Organization and governance using algorithms - Avramopoulos, Ioannis (Digital activism and society., 2023)
Following a recent mathematical, algorithmic, and computational turn in the field of social sciences, and particularly design aspects of contemporary organisations, Organisation and Governance Using Algorithms explores the problem of governance in organisations from a mathematical perspective. Avramopoulos offers a ground-breaking theory and application on organisational systems design, including discussions on organisational systems design requirements, such as productivity, emotion, and reward, the problems of unaccountability, including hierarchical delegation, and the benefits of accountable design. The suggested theoretical approach views organizational actors as computer processors that communicate through a shared infrastructure - both physical and digital - and suggests scientific principles and mechanisms by which to correct inequality and advance democratic governance in organisations.